Results from a mobile outreach influenza vaccination program for vulnerable and high‐risk populations in a high‐income setting: lessons learned - Michelle L. Giles (Australian and New Zealand Journal of Public Health, 2018)
Abstract Objective: The aim of this pilot project was to assess the feasibility of an outreach mobile influenza vaccination program led by a large hospital network targeting high‐risk and vulnerable populations in a high‐income setting. Methods: Key populations were identified and stakeholders with established access to these populations were engaged. A mobile, nurse‐led immunisation service attended sites where these populations attend and offered influenza vaccine. Data was collected on risk factors for severe disease and past vaccination history. Vaccine type and date of administration were entered onto the Australian Immunisation Registry. Results: Sixteen sites were visited, and 520 influenza vaccines were administered. Of those receiving the vaccine, 61% had received it previously, but only 39% in the past 12 months. A total of 232/520 participants (45%) self‐reported a risk factor for severe disease. Conclusions: Appropriate identification of vulnerable populations, with good engagement of key stakeholders, can successfully deliver vaccines to sections of the population who may struggle to engage with healthcare services even when they are freely available. Implications for public health: Taking vaccines to vulnerable populations is well received and remains an important strategy to maximise uptake, even within high‐income settings with universal access to healthcare.